Assessing the impact of economic and energy factors on CO₂ emissions: a case study of Saudi Arabia - Reem A. Alqahtani (Entrepreneurship and Sustainability Issues)
This study seeks to evaluate the applicability of the Environmental Kuznets Curve (EKC) hypothesis in the Saudi Arabian context, a country characterized by its oil-dependent and resource-abundant economy from 1980 to 2022. This study provides insights into Saudi Arabia's progress towards sustainable development by exploring the relationship between CO₂ emissions per capita and economic, demographic, and energy-related factors. The primary objective is determining whether economic growth aligns with environmental sustainability, as outlined in Vision 2030. Utilizing an Autoregressive Distributed Lag (ARDL) model, this study evaluates the short- and long-term relationships between CO₂ emissions per capita and independent variables, including GDP per capita, the squared term of GDP per capita, foreign direct investment (FDI) per capita, energy production per capita, trade openness, and population growth. These findings confirm the existence of an inverted U-shaped relationship between GDP per capita and CO₂ emissions, thereby supporting the EKC hypothesis. Energy generation and population growth significantly contribute to higher pollution levels, and trade openness and FDI positively impact environmental quality by reducing CO₂ emissions. These results highlight the importance of Vision 2030, which emphasizes attracting foreign investment, promoting trade liberalization, and transitioning to renewable energy. This study underscores the need for policymakers to implement comprehensive strategies that support economic growth while achieving long-term environmental sustainability. These findings enhance the understanding of emission dynamics in resource-rich nations and offer valuable guidance for sustainable development planning.